Knowledge, attitude and practices towards oral health among law students in Davangere city: a cross sectional survey - Dummi Jaisubhash, Veeresh; Yavagal, Puja C.; Verma, Prajakta J.; Poornananda; Vijapur, Pooja; Basavaraj, Prathibha (International Journal Of Community Medicine And Public Health, 2024)
Background: Law students play an important role in health promotion and preventive information dissemination among family members and society. A study was done to assess knowledge, attitude practices towards oral health among law students in Davangere city. Aim of the study was to assess knowledge, attitude, and practices related to oral health among law students in Davangere city. Methods: A cross sectional survey was done involving 200 law students of R. L. Law College in Davangere. Data regarding demographic details and knowledge, attitude and practices regarding oral health was collected from research participants using a questionnaire which was tested for validity and reliability. Responses were presented in percentages and Pearson’s correlation test was used for data analysis. Results: Majority (79.5%) of law students had good oral health related knowledge. Majority (93%) of them agreed to the fact that oral health is important for overall health of the body. There was no significant correlation (p>0.05) between knowledge scores and gender and the year of academic course of the law students. Conclusions: Knowledge, attitude and practices towards oral health among law students in Davangere city was fair.